2021
DOI: 10.3389/fpsyt.2021.807563
|View full text |Cite
|
Sign up to set email alerts
|

Parental Chronic Illness, Internalizing Problems in Young Adulthood and the Mediating Role of Adolescent Attachment to Parents: A Prospective Cohort Study

Abstract: Background: Parental chronic illness is associated with an elevated risk for developing social-emotional and behavioral problems in children, in particular internalizing symptoms. This study aimed to investigate the associations between parental chronic illness when participants were adolescents and subsequent internalizing symptoms in young adulthood and whether adolescent attachment to parents or peers mediates these associations.Methods: The study used longitudinal survey data from the Youth and Mental Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Chronic disease was 3.226 times more among female headed families than male-headed families. Previous studies have confirmed that the performance of the family and the management of family problems, such as social, emotional, and behavioral in children, are negatively affected by chronic parental disease [25,26,27,28]. The longer the duration of the disease and its intensity in the parents, the more negative effects on the children [26,27].…”
Section: Discussionmentioning
confidence: 92%
“…Chronic disease was 3.226 times more among female headed families than male-headed families. Previous studies have confirmed that the performance of the family and the management of family problems, such as social, emotional, and behavioral in children, are negatively affected by chronic parental disease [25,26,27,28]. The longer the duration of the disease and its intensity in the parents, the more negative effects on the children [26,27].…”
Section: Discussionmentioning
confidence: 92%
“…The death of one's parents or relatives due to an illness made participants worry about their health. According to (Kaasbøll et al, 2021), the critical condition experienced by parents has a long-term impact on the individual's young adulthood. There is a prolonged negative effect, especially on females rather than male.…”
Section: Discussionmentioning
confidence: 99%